Distributed Kernel-Based Gradient Descent Algorithms - Lin, Shao-Bo; Zhou, Ding-Xuan (Constructive approximation, 2018)
We study the generalization ability of distributed learning equipped with a divide-and-conquer approach and gradient descent algorithm in a reproducing kernel Hilbert space (RKHS). Using special spectral features of the gradient descent algorithms and a novel integral operator approach, we provide optimal learning rates of distributed gradient descent algorithms in probability and partly conquer the saturation phenomenon in the literature in the sense that the maximum number of local machines to guarantee the optimal learning rates does not vary if the regularity of the regression function goes beyond a certain quantity. We also find that additional unlabeled data can help relax the restriction on the number of local machines in distributed learning.